The gift relationship : from human blood to social policy - Titmuss, Richard Morris, 1907-1973 (Policy Press, 2018)
Richard Titmuss (1907-1973) was a pioneer in the field of social administration (now social policy). In 'The Gift Relationship', Titmuss compares blood donations in the US and UK, contrasting the British system of reliance on voluntary donors to the American one in which the blood supply is in the hands of for-profit enterprises. He concludes that a system based on altruism is both safer and more economically efficient.